A study on solid waste generation and composition from commercial sources (case study: Taman Tas Kuantan) - Lyntia, Ping Jawa (2012)
Solid waste is a useless material and unwanted material products that is no longer use and has been discarded by the society. However, the increasing of the population in our country is obviously affecting the production of solid waste especially from commercial sources. This study will determine the solid waste generation and composition of commercial sources at Taman Tas Kuatan, factors that affecting solid waste generation and review the solid waste management at Taman Tas. Ten premises are randomly chosen as the samples and they are classified into two types of premises which are product premises and service premises. Methods that are used to collect the data were through field work and questionnaires. The data was collected within one month which is on 18th March 2012 until 14th April 2012. The result shows that service premises contributed the highest solid waste generation rate which is 6.21 kg/commercial unit.day while product premises only contributed 3.8lkg/commercial unit.day. The highest solid waste generated from commercial sources at Taman Tas Kuantan is food and organic waste which is 76% where it was mostly generated by service premises. This is because of size of the population, level of standard living, waste separation or recycles at source and the influenced of the events. Education to the society is also essential to give awareness and education to reduce the generation of solid waste at Taman Tas Kuantan.